Analisa Faktor Waktu Tunggu Pelayanan Resep di Rumah Sakit Pekanbaru Medical Center - Mulya, Adrian; Ennimay, Ennimay; Devis, Yesica (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: The results of the Walk Through Audit (WTA) BPJS stated that the waiting time for talking out the drugs at the Pekanbaru Medical Center Hospital was one of the factors for the lateness of services to patients. After conducting a preliminary study, the data was found that the waiting time for taking out the drugs was over than minimum value of Standard Service. The purpose of this study was to analyze the factors that affected the waiting time for outpatient prescription drug services at Pekanbaru Medical Center Hospital. This study used a combination method (Mixed-Methods Sequential Explanatory Design), namely by combining quantitative and qualitative descriptive methods. From 70 samples obtained quantitative research data for type of patient, type of prescription, number of items in prescription, number of prescriptions in shifts and number of prescriptions based on drug availability which were not factors that affected the waiting time for outpatient drug prescription services, this was based on the test All Chi-Square values ​​> 0.05, this meant that Ho was rejected or in other words it was not proved related to the waiting time of service. On the other hand the qualitative research with in-depth interviews and observations resulted in insufficient number of human resources, lack of human resource competence, unclear service process flow, inadequate facilities and infrastructure, especially the Sim-PEC network system and pharmacy installation room layout which haven’t fulfilled the standard caused the lateness of services or the length duration of waiting time for outpatient drug service became longer.